2010
DOI: 10.1093/pasj/62.5.1135
|View full text |Cite
|
Sign up to set email alerts
|

Fibre Multi-Object Spectrograph (FMOS) for the Subaru Telescope

Abstract: Fibre Multi-Object Spectrograph (FMOS) is the first near-infrared instrument with a wide field of view capable of acquiring spectra simultaneously from up to 400 objects. It has been developed as a common-use instrument for the F$/$2 prime-focus of the Subaru Telescope. The field coverage of 30$^\prime$ diameter is achieved using a new 3-element corrector optimized in the near-infrared (0.9–1.8$\ \mu$m) wavelength range. Due to limited space at the prime-focus, we have had to develop a novel fibre positioner, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 31 publications
1
64
0
Order By: Relevance
“…IR-selected sources were targeted in two pointings (0.5 deg 2 ) located within the COSMOS field with FMOS as part of the Guaranteed time observations program. The FMOS instrument (Kimura et al 2010) consists of 400 1.2 arcsec diameter fibres which can be placed within a 30 arcmin diameter field of view. We used the low-resolution mode (R ∼ 600), allowing instantaneous coverage of both the J and H band (0.9 < λ < 1.8 µm), with cross-beam switching, i.e.…”
Section: Fmos Observations and Emission-line Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR-selected sources were targeted in two pointings (0.5 deg 2 ) located within the COSMOS field with FMOS as part of the Guaranteed time observations program. The FMOS instrument (Kimura et al 2010) consists of 400 1.2 arcsec diameter fibres which can be placed within a 30 arcmin diameter field of view. We used the low-resolution mode (R ∼ 600), allowing instantaneous coverage of both the J and H band (0.9 < λ < 1.8 µm), with cross-beam switching, i.e.…”
Section: Fmos Observations and Emission-line Measurementsmentioning
confidence: 99%
“…Here we investigate the rest-frame optical-to-far-IR properties of a sample of Herschel 1 (Pilbratt et al 2010) sources which were targeted for near-IR spectroscopy with FMOS (Kimura et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This configuration with a large distance between fibers and the metrology camera allows us to take all fiber images in one shot, although the possible disturbing effects of the air between them merits careful attention. In 2012 December this "dome seeing" effect was measured at Subaru telescope by using the basically same configuration but actually backilluminated FMOS 27 fibers and a commercial-based CCD camera Atik 450 set at the common-use Cassegrain container ( Figure 11). It was concluded that to average out the short-timescale image instability on fiber positions due to the "dome seeing" effects an exposure time of around 1 second or so rather than shorter ones is optimal.…”
Section: Metrology Cameramentioning
confidence: 85%
“…The light passing through the turbulence will deviate from its original position on the camera sensor. In order to understand such effect, a series of tests were executed with Subaru FMOS 4 instrument under different conditions. The details are discussed in the following section:…”
Section: Metro Logy System Analysismentioning
confidence: 99%